IMPLEMENTASI KEPEMIMPINAN SPIRITUAL PENDIDIKAN BERBASIS MASYARAKAT - Indrayani, Rusmiati (STIT Ibnu Rusyd Tanah Grogot, 2025)
Spiritual leadership is a form of leadership style that emphasizes on the way to get the pleasure of God. This study’s objective is to describe the implementation of spiritual leadership in a form of society-based education called majelis ta’lim. The research method is qualitative with case study approach. Collecting observation data, document study, and interview with participant analyzed by data reduction process, data presentation, and drawing conclusions. The result shows that (1) Spiritual leadership that emphasize on ruhiyyah morality and call of conscinesness has ability to set actual leadership style. Exemplary behaviour exemplified by a leader such as deepening knowledge about divinity and put into practice enable to form strong beliefs (yaqin). (2) among the characteristic of leader that has spiritual leadership is the set of capacity to prioritizing cleanliness of heart, protecting oneself from dishonorable actions (wara’), and refrain from the dazzling temptations of the world (zuhud). (3) leader’s skills in communicating spiritual values such as yaqin, wara’, and zuhud has ability to grows collective consciousness in member of majelis ta’lim.